Finding the Reasons Behind The Use of English Slang Words By Generation Alpha on TikTok Videos - Kirana Fitri Wulandari (fakultas ilmu budaya, 2025)
This study discusses about the use of English slang words by Generation Alpha on MRCI.TV’s TikTok videos. It aims to discover the motive behind the use of English slang words by Generation Alpha by seeing from the hearer oriented using Mattiello’s (2008) theory that consist of five features. There are Playfulness and Humor, Desire to Impress and Faddishness, Freshness and Novelty, Colour and Musicality, and Impertinence, Offensiveness, and Aggressiveness. Additionally, qualitative method is used for conduct this research for describing the data that is found. It is the slang words that are used on MRCI.TV’s TikTok videos. This study only focuses on the slang words that are used on five videos that are chosen on MRCI.TV accounts. There are fourteen different slangs found on the chosen videos. The results of the study indicate that most of the slang that appears in the five selected videos on the MRCI.TV TikTok account falls into the categories of Impertinence, Offensiveness, and Aggressiveness. The number of expressions consisting of this type of slang, based on the motive for its use, is four expressions. This indicates that the use of slang by Generation Alpha is primarily aimed at provoking the audience. However, another purpose is to convey the speaker's true emotions to the audience. Ultimately, this type of slang is used by Generation Alpha to express their feeling freely and confidently.
Finding the Reasons Behind The Use of English Slang Words By Generation Alpha on TikTok Videos
Reupload file repository 6 februari 2026_agus/feren -
Keywords: gen alpa; vidio tiktok